Metastasis and cachexia: alongside in clinics, but not so in animal models. Issue 6 (22nd August 2019) - Tomasin, Rebeka; Martin, Ana Carolina Baptista Moreno; Cominetti, Márcia Regina
Abstract: Cancer cachexia is a paraneoplastic syndrome characterized by lean mass wasting (with or without fat mass decrease), culminating in involuntary weight loss, which is the key clinical observation nowadays. There is a notable lack of studies involving animal models to mimic the clinical reality, which are mostly patients with cachexia and metastatic disease. This mismatch between the clinical reality and animal models could at least partly contribute to the poor translation observed in the field. In this paper, we retrieved and compared animal models used for cachexia research from 2017 and 10 years earlier (2007) and observed that very little has changed. Especially, clinically relevant models where cachexia is studied in an orthotopic or metastatic context were and still are very scarce. Finally, we described and supported the biological rationale behind why, despite technical challenges, these two phenomena—metastasis and cachexia—should be modelled in parallel, highlighting the overlapping pathways between them. To sum up, this review aims to contribute to rethinking and possibly switching the models currently used for cachexia research, to hopefully obtain better and more translational outcomes.